PROBLEMS OF USING GAME EDUCATIONAL TECHNOLOGIES IN PRESCHOOL EDUCATIONAL INSTITUTIONS - Erkhanova Nasiba Absaitovna (Western European Studies, 2024)
Innovative technologies in the preschool education system are used primarily to solve pressing issues, improve the quality of services provided, meet the growing demands of parents, as well as increase the competitiveness of preschool organizations. This article analyzes the relevance of the use of game technology in preschool education organizations.
Keywords: Game technology; didactic games; games monitoring card used in educational activities